The Cooperation of UNHCR and Indonesia on Afghan Refugee Handling in Indonesia - Nurul Adhaniah; Dudy Heryadi; Deasy Silvya Sari (Department of International Relations, Universitas Andalas, 2021)
Afghan refugees are currently the largest number of refugees in Indonesia. As a country that has not ratified the 1951 Refugee Convention, Indonesia does not have the right obligations and legal basis in dealing with refugee problems. Thus, Afghan refugees lose their basic human rights. Therefore, UNHCR and Indonesia must work together and share responsibilities in providing protection to refugees. The author uses the concept of refugees, international organizations and international cooperation to study secondary data that is collected and analyzed qualitatively. The data used relates to the condition of Afghan refugees in Indonesia, the role of UNHCR, and the collaborative process of UNHCR and the Indonesian government in handling Afghan refugees in Indonesia. This article finds that the work of UNHCR and the Government of Indonesia is carried out by adjusting actions through a policy coordination process and agreement on the scope of cooperation and setting an agenda that is in line with the objectives and programs to achieve temporary protection and empowerment of refugees. This cooperation results in the protection of the human rights of Afghan refugees, such as human rights at the shelter, other rights such as access to education for refugee children and transparency regarding the personal data of refugees registered in Indonesia for further empowerment solutions.